Advances and challenges in alkaline anion exchange membrane fuel cells. (May 2018) - Pan, Z.F.; An, L.; Zhao, T.S.; Tang, Z.K.
Abstract: The last several decades have witnessed the rapid development of alkaline anion exchange membrane fuel cells (AAEMFCs) that possess a series of advantages as compared to acid proton exchange membrane fuel cells, such as the enhanced electrochemical kinetics of oxygen reduction reaction and the use of inexpensive non-platinum electrocatalysts, both of which are rendered by the alkaline medium. As an emerging power generation technology, the significant progress has been made in developing the alkaline anion exchange membrane fuel cells in recent years. This review article starts with a general description of the setup of AAEMFCs running on hydrogen and physical and chemical processes occurring in multi-layered porous structure. Then, the electrocatalytic materials and mechanisms for both hydrogen oxidation and oxygen reduction are introduced, including metal-based, metal oxide-based, and non-metal based electrocatalysts. In addition, the chemistries of alkaline anion exchange membranes (AAEMs), e.g. polymer backbone and function groups, are reviewed. The effects of pre-treatment, carbonate, and radiation on the performance of AAEMs are concluded as well. The effects of anode and cathode ionomers, structural designs, and water flooding on the performance of the single-cell are explained, and the durability and power output of a single-cell are summarized. Afterwards, two innovative system designs that are hybrid fuel cells and regenerative fuel cells are presented and mathematical modeling on mass transport phenomenon in AAEMFCs are highlighted. Finally, the challenges and perspectives for the future development of the AAEMFCs are discussed.